2000
DOI: 10.4049/jimmunol.165.5.2764
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Human Leukocytes Reduces Surface P-Selectin Glycoprotein Ligand-1 (PSGL-1, CD162) and Adhesion to P-Selectin In Vitro

Abstract: P-selectin glycoprotein ligand-1 (PSGL-1), the primary ligand for P-selectin, is constitutively expressed on the surface of circulating leukocytes. The objective of this study was to examine the effect of leukocyte activation on PSGL-1 expression and PSGL-1-mediated leukocyte adhesion to P-selectin. PSGL-1 expression was examined via indirect immunofluorescence and flow cytometry before and after leukocyte stimulation with platelet activating factor (PAF) and PMA. Human neutrophils, monocytes, and eosinophils … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
102
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(115 citation statements)
references
References 40 publications
(44 reference statements)
10
102
3
Order By: Relevance
“…It has been suggested that the way SELPLG is distributed on the leukocyte surface, and not the amount, is important for adhesion of leukocytes to P-selectin (Bruehl et al 1997;Lorant et al 1995). Moreover, SELPLG in the circulation could derive either from the release of SELPLG from leukocyte surfaces or from its release after the initiation of leukocyte rolling (Davenpeck et al 2000). In the first case, higher circulating levels would reflect decreased leukocyte binding capacity to P-selectin, and would be associated with a lower risk of CAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the way SELPLG is distributed on the leukocyte surface, and not the amount, is important for adhesion of leukocytes to P-selectin (Bruehl et al 1997;Lorant et al 1995). Moreover, SELPLG in the circulation could derive either from the release of SELPLG from leukocyte surfaces or from its release after the initiation of leukocyte rolling (Davenpeck et al 2000). In the first case, higher circulating levels would reflect decreased leukocyte binding capacity to P-selectin, and would be associated with a lower risk of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…SELPLG is a dimeric mucinlike glycoprotein expressed on all leukocyte surfaces, constituted by two monomers of molecular mass of ∌ 120-kDa (Moore et al 1992). A human soluble SELPLG has been described which is released after leukocyte activation (Davenpeck et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The reports that PSGL-1 can be processed by a protease [15,16] and that PSGL-1 could be a candidate substrate for ADAM8 [17], in addition to our finding of PSGL-1/ADAM8 association, prompted us to investigate the potential involvement of ADAM8 in the cleavage of PSGL-1. Experiments with neutrophils incubated with activated sADAM8 showed a significant diminution in the membrane expression of PSGL-1 ( Fig.…”
Section: Proteolytic Cleavage Of Psgl-1 By Adam8mentioning
confidence: 99%
“…These processes are critical for eosinophil interaction to activated vascular endothelium as well as for migration and tissue localization and are also implicated in a range of effectors functions by these cells (Schleimer et al 1992 (Davenpeck et al 2000). The hypothesis that the primary function of eosinophils is to defend hosts against infection by relatively large organisms such as parasitic helminths is based on the accumulation of observations that: (1) eosinophils degranulation can kill helminths in vitro in the presence of antibody and/or complement; (2) they move from the blood and aggregate in the locality of helminths in vivo; (3) large numbers of eosinophils are often seen in close association with both intact and damaged helminths in vivo; and (4) they clearly degranulate in the vicinity of, or on to the surfaces of, helminths in vivo (Butterworth 1984).…”
Section: Herein We Have Focused Attention On Major Phenotypic Featurementioning
confidence: 99%
“…Besides L-selectin (CD62-L), the major molecule expressed on the surface of circulating leukocyte (Bevilacqua & Nelson 1993, Tedder et al 1995, eosinophils express a large number of adhesion molecules including integrins (LFA-1/CD18) and members of the immunoglobulin superfamily, such as ICAM-1 (CD54) (Bochner & Schleimer 1994). The counterligants for the selectins share common features of carbohydrate ligands for selectins, named Lewis X -related structures (Davenpeck et al 2000).…”
mentioning
confidence: 99%